MANAJEMEN MUTU PENINGKATAN DAYA SAING LULUSAN PERGURUAN TINGGI BERBASIS PESANTREN - Ahmad Zarkasyi (STIS MIFTAHUL ULUM LUMAJANG PRESS (STISMU PRESS), 2022)
This article reveals the contribution of the education quality system in increasing the competitiveness of Miftahul Ulum Lumajang Islamic Boarding School graduates. This type of research is qualitative with a case study approach, data obtained from interviews, observations, and documentation, then analyzed by condensing, displaying data, and drawing conclusions. The research findings show that quality of the Miftahul Ulum Lumajang Islamic Boarding School education system begins with the integration of visions between institutions under the auspices of the Miftahul Ulum Lumajang Foundation. They were followed by setting goals and strategies for improving the academic quality of students through three models of quality development, namely coaching in the recitation, extracurricular activities, and activities in the pesantren environment. Keywords: quality managemeny, the competitiveness of graduates, College University, pesantren.